Development of Triphala-Arishtaka Kwatha as an ayurvedic antiseptic and cleansing agent - Praveen Kumar Yadav; Pradeep S Shindhe; Rudramma R Hiremath; K P Skandhan (Wolters Kluwer Medknow Publications, 2023)
Introduction: Antiseptics are vital in surgery. Triphala kwatha is being used as a wound-cleaning solution since years and is a known antimicrobial agent against some microbes. Arishtaka is easily available and has lekhana, kusthaghna, and vishanasana properties. Saponin is the main chemical constituent of arishtaka which produces froth. The aim of the study was to formulate an innovative preparation by combining triphala and arishtaka to evaluate its antiseptic and cleansing activity against selected human pathogens and establish it as an antiseptic and cleansing agent. Methods: Three different ratios of Triphala-Arishtaka kwatha (TAK) samples were prepared with different ratios of arishtaka (1:1:1:2[T1], 1:1:1:1[T2], and 1:1:1:0.5[T3]) and were subjected to physicochemical, phytochemical, antimicrobial, and antiseptic studies. Results: Out of the three samples of TAK, T3 showed better results with respect to antiseptic and cleansing properties. Antimicrobial study results showed that the antimicrobial activity of T3 was comparable to that of 5% povidone-iodine (PI) solution and the overall antiseptic activity of T3 is better than that of 5% PI solution. The cleansing activity was assessed by calculating the foaming indexes of the samples and all the samples of the TAK showed a value for more than 10,000, whereas the value for Savlon solution was 1000. Conclusion: Triphala-Arishtaka combination of 1:1:1:0.5(T3) has shown better antimicrobial activity against Streptococcus pyogenes, Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa, comparable to that of 5% PI solution. Overall it has also shown better antiseptic activity against S. aureus and E. coli and it has better cleansing activity than Savlon solution.